ChemInform Abstract: Palladium‐Catalyzed Arylation of β‐Methylene C(sp3)—H Bonds at Room Temperature: Desymmetrization of Simple Cycloalkyl Carboxylic Acids. Issue 37 (August 2016) - Nack, W. A.; Wang, B.; Wu, X.; Jiao, R.; He, G.; Chen, G.
Abstract: In most cases, the β methylene C—H bonds of cycloalkylcarboxamides of varied ring size are monoarylated giving products with excellent cis‐diastereoselectivity whereby, diarylated products are also observed as by‐products.